PENGARUH LAMA SIMPAN DAN WARNA KERABANG TELUR AYAM RAS TERHADAP INDEKS ALBUMEN, INDEKS YOLK, DAN pH TELUR - Sekar Putri Hiroko; Tintin Kurtini; Riyanti . (JURNAL ILMIAH PETERNAKAN TERPADU, 2014)
Purebred chicken egg is the most favorable egg in the society. This egg usually will be damageafter 14-days of storage. Beside of the storage duration, the internal quantity of egg has also beenaffected by quality of eggshell. The quality of eggshell include the eggshell thickness and amount ofeggshell pores. The amount of eggshell pores can be identified by means of eggshell color. The poreshave a role on the CO2 evaporation process, which give effect to the albumen index, yolk index, andegg’s pH.The purposes of the research are to know the best effect of storage duration and eggshell colorto albumen index, yolk index, and egg’s pH. This research was done on April 10-24th, 2014, usecomplete randomize block design with 2x2 of nested model. The main block is storage duration (P1: 7days and P2: 14 days) and the partial block is eggshell’s color (W1: light brown and W2: dark brown)with 5 times replication. The observed variable in this research are albumen index, yolk index, andegg’s pH. The research’s data were analyzed by using Analysis of variance test and 5% error levelDuncan test.The research result shown that storage duration and eggshell color have significant effect(P<0,05) toward albumen index, yolk index, and egg’s pH. The 7 days storage for light browneggshell color and dark brown eggshell color have good quality of albumen index, yolk index, andegg’s pH.